The yin and yang of intestinal epithelial cells in controlling dendritic cell function - Iliev, Iliyan D. (The Rockefeller University Press, 2007)
Recent work suggests that dendritic cells (DCs) in mucosal tissues are “educated” by intestinal epithelial cells (IECs) to suppress inflammation and promote immunological tolerance. After attack by pathogenic microorganisms, however, “non-educated” DCs are recruited from nearby areas, such as the dome of Peyer's patches (PPs) and the blood, to initiate inflammation and the ensuing immune response to the invader. Differential epithelial cell (EC) responses to commensals and pathogens may control these two tolorogenic and immunogenic functions of DCs.